Hypoglycemia in preterm babies Incidence and risk factors - Asril Aminullah; Dita Setiati; Sudigdo Sastroasmoro (Indonesian Pediatric Society, 2001)
Hypoglycemia is one of the most common problems in neonates, especially in preterm babies. Although in themajority of cases the outcome is good, symptomatic or asymptomatic hypoglycemia may give significant complications thatmay cause death or developmental delay later in life. We conducted a cross sectional study from September 5, 1999 throughMay 8, 2000 to identify factors associated with hypoglycemia in preterm babies treated at the Division of Perinatology, CiptoMangunkusumo Hospital, Jakarta. There were 112 babies included in the study, with the mean gestational age of 33.3 (range22 to 37, SD 4.2) weeks, and mean birth weight of 1801 (range 850 to 2440, SD 420) grams. Twenty-seven of the 112 infantsshowed hypoglycemia. Univariate analysis disclosed that birth weight, degree of perinatal asphyxia, small for gestational age(SGA), presence of respiratory distress syndrome, mothers with preeclampsia or eclampsia, and mothers who had intravenousinfusion of glucose during labor were significantly associated with hypoglycemia in preterm babies. Gestational age,meconium staining, or infant of diabetic mother were not significantly associated with neonatal hypoglycemia. On logisticregression analysis to control confounders we found that only the degree of perinatal asphyxia and small for gestational agewere associated with hypoglycemia in those preterm babies.